The Impact of Information Technology Development on Cybercrime Rate in Indonesia - Ni Komang Novia Widiasari; Emmy Febriani Thalib (Journal of Digital Law and Policy, 2022)
Information technology is growing rapidly in society. In the period of technological development not only gives us a positive impact, but can also have a negative impact. One of the negative impact of the development of information technology is the misuse of the technology, so that it can harm others. Technological developments have an effect on the occurrence of cybercrime in Indonesia, the crimes that have occurred have also developed and varied. The method used in this research are a qualitative approach and descriptive methods. The results of the study show the impact of Information Technology development on the level of cybercrime in Indonesia occurs such as loss of privacy, unauthorized access to important data, data theft and others. Prevention and countermeasures that can be carry out to prevent cybercrime are preventive, pre-emptive and repressive measure